Preparation method of solid electrolyte for lithium metal battery
By using polymer-covalent organic framework (COF) solid electrolyte integrated with homoimide bond molecules in lithium metal batteries, the problem of limited performance of solid electrolytes in lithium metal batteries in the prior art is solved, and efficient Li+ transmission and stable interface contact are achieved, which significantly improves the performance of lithium metal batteries.
Patent Information
- Application Number
- CN202510645882.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-20
- Publication Date
- 2025-06-20
- Estimated Expiration
- 2045-05-20
AI Technical Summary
The solid electrolytes of existing lithium metal batteries are difficult to achieve high ionic conductivity, stable interface contact and mechanical strength at room temperature, resulting in limited performance of lithium metal batteries.
Through homologous imide bond molecules, the ion conduction pathway is integrated and combined with the polymer-covalent organic framework (COF) structure is formed to form a continuous ion conduction pathway, a unified chemical interface and stable electrode compatibility.
It achieves efficient Li+ transmission at room temperature, improves ion selectivity and thermal stability, and significantly improves the performance and stability of lithium metal batteries.
Smart Images

Figure CN120184361A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium batteries, and specifically to a preparation method of a solid electrolyte for a lithium metal battery. Background Art
[0002] Lithium (Li) metal batteries (LMBs) are considered attractive next-generation energy storage devices because Li metal has an extremely high theoretical capacity (3860 mAh g −1 ) and a low redox potential (−3.04 V vs standard hydrogen electrode). However, the commercialization of lithium metal batteries using organic electrolyte systems is severely limited by safety issues and ongoing challenges associated with lithium metal anodes, including uncontrolled dendrite formation, dead lithium accumulation, and large volume fluctuations during cycling. To address these challenges, extensive research has been conducted by researchers in the field, such as porous scaffolds, artificial solid electrolyte interphase layers, and solid state electrolytes (SSEs). Among these methods, SSEs have attracted particular attention due to their inherent safety and potential to suppress Li dendrites.
[0003] Covalent organic frameworks (COFs) have a highly tunable chemical structure and well-defined porosity and have emerged as competitive candidate materials for next-generation SSEs, providing a unique platform for designing efficient lithium ion conductors. The characteristic stacking of COFs enables the formation of oriented open channels throughout the COF framework, facilitating oriented ion migration. To date, various COF-based solid electrolytes have been developed, including anion COFs, cation COFs, zwitterionic COFs, and PEO-inserted COFs, plasticizer-COF composites. These materials have demonstrated efficient ion conduction behavior by introducing mobile charge carriers and altering the internal pore environment, thereby enhancing the dissolution and mobility of Li. However, most of them exhibit limited room temperature ionic conductivity and cycling performance in all-solid-state LMBs. Therefore, a new strategy is still needed for high-performance all-solid-state lithium metal batteries to fabricate COF solid electrolytes that can effectively promote ion pair dissociation and ion component transport. Summary of the Invention
[0004] Although current solid-state polymer electrolytes (SPEs) and solid-state inorganic electrolytes (SIEs) have promising prospects, they still face inherent limitations and cannot meet the various requirements of solid-state LMBs. Compared with SIEs, solid-state polymer electrolytes (SPEs) such as poly(ethylene oxide) (PEO) exhibit more superior interfacial compatibility and processability. However, the ion transport mechanism depends on the coupling of lithium migration and polymer segment motion, resulting in insufficient ionic conductivity (<10−4 S cm −1) and low lithium transference number (0.2 - 0.5). To alleviate these problems, traditional solid polymer electrolytes usually operate at high temperatures to promote segmental motion and increase ionic conductivity. However, this approach compromises the mechanical integrity of the battery, leading to reduced structural stability and safety issues. Despite various strategies such as adding inorganic fillers, crosslinking polymers, introducing flame retardants, and designing and synthesizing block copolymers, the balance among the ionic conductivity, lithium transference number, and physicochemical stability exhibited by the materials still continues to trouble the industry. This long-term challenge highlights the urgent need for innovative methods to develop SSEs that can simultaneously achieve efficient Li + transport, high ionic selectivity, and excellent thermal stability.
[0005] To achieve the above object, the present invention provides the following technical solutions: A preparation method of a solid electrolyte for a lithium metal battery, comprising the following steps: Synthesis of PI: Under an inert gas, 4 mmol of 2,4,6-trimethyl-1,3-phenylenediamine and 10 mL of N,N-dimethylacetamide (DMAc) are added to a three-necked flask equipped with a mechanical stirring device. Then, 3.8 mmol of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) and 0.2 mmol of 4,4'-(ethyne-1,2-diyl)diphthalic anhydride are successively added and mechanically stirred until a viscous polyamic acid is formed. Then, 4.8 mL of acetic anhydride and 4 mL of pyridine are slowly added to the polyamic acid, and stirred at room temperature to obtain a mixture. The mixture is slowly poured into a methanol aqueous solution to obtain an intermediate product. The intermediate product is crushed and washed with a methanol aqueous solution, and then dried under vacuum to obtain a PI polymer; Synthesis of COF: 0.15 mmol of pyromellitic acid, 0.60 mmol of benzoic acid, and 0.10 mmol of 1,3,5-tris(4-aminophenyl) compound are reacted at 180 - 210 °C for 5 days. The product is washed and subjected to Soxhlet extraction with tetrahydrofuran, and then dried under vacuum to obtain COF; Synthesis of the solid electrolyte: COF is immersed in a 1 mol / L LiTFSI (lithium bis(trifluoromethanesulfonyl)imide) acetonitrile solution, washed, and dried under vacuum to obtain an NKCOF compound. The NKCOF compound, PI polymer, and LiTFSI powder are dissolved in DMAc to form a casting solution, which is then filtered, spread out, and the solvent is evaporated under vacuum conditions to obtain a thin film. Finally, it is soaked in methanol and then dried to obtain the finished product.
[0006] As a further aspect of the present invention: The inert gas is argon.
[0007] As a further aspect of the present invention: The time of mechanical stirring is 48 h, and the time of stirring at room temperature is 24 h.
[0008] As a further solution of the present invention: the volume ratio of methanol to water in the methanol aqueous solution is 1:1, and the number of times of washing with the methanol aqueous solution is 5 times.
[0009] As a further solution of the present invention: the temperature of vacuum drying is 80 degrees Celsius.
[0010] As a further solution of the present invention: the 1,3,5-tris(4-aminophenyl) compound is one of 1,3,5-tris(4-aminophenyl)benzene, 1,3,5-tris(4-aminophenyl)azine, and 1,3,5-tris(4-aminophenyl)amine.
[0011] As a further solution of the present invention: the NKCOF compound is one of NKCOF-28, NKCOF-29, and NKCOF-30.
[0012] As a further solution of the present invention: the filtration and spreading are carried out using a polytetrafluoroethylene surface dish (10 cm×10 cm).
[0013] Compared with the prior art, the beneficial effects of the present invention are: The present invention integrates the ion conduction pathway through a homologous imide bond molecule, and the polar microenvironment enables the Li + / TFSI − transport to have a structurally selective decoupling, solving the long-term problem in the design and application fields of solid-state electrolytes (SSEs) for lithium metal batteries - achieving high ionic conductivity, stable interfacial contact, and mechanical strength simultaneously at room temperature, and preparing a polymer-covalent organic framework (COF) solid-state electrolyte constructed by homologous imide bonding. This molecular integration architecture can form a continuous ion conduction path, a unified chemical interface, and stable electrode compatibility, providing a new design strategy for high-performance SSEs. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is a flowchart of the preparation method of the solid-state electrolyte for lithium metal batteries.
[0015] Figure 2 is a schematic diagram of the synthesis of three representative imide-bonded COFs.
[0016] Figure 3 is a PXRD and nitrogen adsorption data graph of three representative imide-bonded COFs.
[0017] Figure 4HR-TEM images of three representative imide-bonded COFs. Among them, a and b are related images of NKCOF-28, c and d are related images of NKCOF-29, and e and f are related images of NKCOF-30.
[0018] Figure 5 Fourier transform infrared spectroscopy diagrams of three representative imide-bonded COFs. Among them, a is the related image of NKCOF-28, b is the related image of NKCOF-29, and c is the related image of NKCOF-30.
[0019] Figure 6 Solid-state nuclear magnetic resonance results diagrams of three representative imide-bonded COFs. Among them, a is the related image of NKCOF-28, b is the related image of NKCOF-29, and c is the related image of NKCOF-30.
[0020] Figure 7 Schematic diagrams of the composite morphology of PI, PI@COF0.5, and PI@COF.
[0021] Figure 8 Results diagrams of the ionic conductivity and activation energy of PI, PI@COF0.5, and PI@COF.
[0022] Figure 9 Results diagrams of the lithium ion transference number and electrochemical window of PI, PI@COF0.5, and PI@COF.
[0023] Figure 10 Results diagrams of the critical current density of three Li / Li symmetric batteries.
[0024] Figure 11 Results diagrams of the Li deposition / stripping experiments of three Li / Li symmetric batteries.
[0025] Figure 12 Results diagrams of the long-term cycling stability test data of the Li / PI@COF / Li symmetric battery.
[0026] Figure 13 Results diagrams of the discharge capacities of solid-state batteries with different component electrolytes at 0.2 C.
[0027] Figure 14 Data diagrams of the battery cycling stability and capacity retention rate of three batteries.
[0028] Figure 15 Results diagrams of the rate capabilities of batteries using PI, PI@COF0.5, and PI@COF electrolytes. Detailed implementation methods
[0029] The following will clearly and completely describe the technical solutions in the embodiments of the present invention with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without making creative efforts belong to the scope of protection of the present invention.
[0030] Preparing a high-performance polymer COF solid electrolyte with a homologous imide bond requires a reasonable selection of the COF framework and a polymer matrix rich in imide. In this application, three representative imide-bonded COFs (NKCOF-28, NKCOF-29, and NKCOF-30) were first selected and synthesized to systematically evaluate their suitability as the COF skeletons for solid electrolyte construction. Using tris(4-aminophenyl)amine (TAPA), 1,3,5-tris(4-aminophenyl)benzene (TAPB), and 2,4,6-tris(4-aminophenyl)-triazine (TAPT) as linkers, three structurally related COF models as shown in Figure 2 were constructed.
[0031] Crystal structure analysis was performed on these three structurally related COF models. Figure 3 Figures Figure 3 show the powder X-ray diffraction (PXRD) and nitrogen adsorption data graphs of these three structurally related COF models. It can be seen from 2 that all imide-linked COFs have good crystal structures, showing sharp peaks at low angles, which match very well with the simulated pattern of the overlapping AA stacking mode. The permanent porosity of the COFs was evaluated by nitrogen adsorption-desorption experiments. All adsorption isotherms showed typical type-IV characteristics, i.e., the characteristics of mesoporous materials. The BET surface areas of NKCOF-28, NKCOF-29, and NKCOF-30 were 941 m 2 / g, 1025 m 2 / g, and 1234 m 2 / g, respectively. This result indicates that there are long-range ordered crystal channels in these imide-bonded COFs, which are beneficial to the transport of Li + .
[0032] These three structurally related COF models were photographed using high-resolution transmission electron microscopy (HR-TEM). Figure 4 Figure Figure 4 shows the HR-TEM images. It can be seen from
[0033] that all three COFs have good crystallinity and the pore morphology is clearly visible. Figure 5 Figure Figure 6Solid-state NMR results of three COFs.
[0034] NKCOF compounds, PI polymers, and LiTFSI powders were mixed in different mass ratios (0:1:0.2, 0.5:1:0.2, and 1:1:0.2) to prepare polymer-COF solid electrolytes, obtaining PI, PI@COF0.5, and PI@COF, respectively. Figure 7 Schematic diagrams of the composite morphologies of PI, PI@COF0.5, and PI@COF. Since Li + ions also migrate between ligand sites through the segmental motion of amorphous polymer chains, similar to the conduction behavior of other polymers. After forming the polymer COF solid electrolyte, the number of ion adsorption sites and charge carriers is expected to increase significantly, and its ion conduction behavior is also expected to change.
[0035] The ionic conductivities and activation energies of PI, PI@COF0.5, and PI@COF were measured, and the test results are shown in Figure 8 . From Figure 8 it can be seen that the ionic conductivity at room temperature is in the order of PI (6.0×10 −5 S cm −1 ) < PI@COF0.5 (1.5×10 −4 S cm −1 ) < PI@COF (3.3×10 −4 S cm −1 ), indicating that PI@COF has an advantage in promoting Li + conduction and helps to form a continuous conductive network through homologous imide bonds between the COF skeleton and polymer chains. Compared with most reported COF-based composite polymer electrolytes, PI@COF exhibits significantly enhanced ionic conductivity. In addition, the activation energies of PI, PI@COF0.5, and PI@COF are 0.35 eV, 0.22 eV, and 0.14 eV, respectively, indicating that the migration barrier for Li + transport in PI@COF is lower.
[0036] DC polarization and AC impedance were performed on PI, PI@COF0.5, and PI@COF, and the results are shown in Figure 9 . From Figure 9 it can be seen that PI@COF exhibits a smaller interfacial resistance, lower charge transfer resistance, and higher tLi + than PI and PI@COF0.5. This indicates that combining polymers and COFs with homologous imide bonds will form a stable electrode / electrolyte interface and enhance Li +Directional migration. Linear sweep voltammetry (LSV) shows that PI@COF has a high electrochemical stability of greater than 4.6 V, indicating that PI@COF significantly improves the Li + conductivity and increases the Li + mobility, making it an electrolyte material suitable for solid-state lithium metal batteries.
[0037] PI, PI@COF0.5, and PI@COF were applied in Li / Li symmetric batteries, and then their critical current density (CCD) was measured. The critical current density (CCD) of the Li / Li symmetric battery was determined by constant current cycling with a stepwise increase in current density. A value of 0.1 mA cm -2 was set as the step value, and the holding time was one hour for each step. The measurement results are shown in Figure 10 , and it can be seen from Figure 10 that the voltage of the Li / PI / Li battery suddenly dropped at 0.8 mA cm -2 , indicating a failure of the Li / Li symmetric battery. The CCD of the Li / PI@COF / Li battery was 1.4 mA cm -2 , which was much higher than the test values of PI and PI@COF0.5, which were 0.8 mA cm -2 and 1.0 mA cm -2 , respectively.
[0038] Then, Li deposition / stripping experiments and long-term cycling stability tests were carried out on the Li / Li symmetric battery. The results are shown in Figure 11 and Figure 12 . The Li deposition / stripping experiment can study the stability between the solid electrolyte and the Li metal interface. It can be seen from Figure 11 and Figure 12 that the Li / Li symmetric battery with PI@COF showed stable and reliable lithium plating / stripping behavior for more than 2000 hours, without obvious increase and irreversible fluctuations in overpotential at a current density of 0.1 mA cm -2 , indicating significantly superior cycle life. In contrast, the batteries derived from PI and PI@COF0.5 showed a rapid increase in voltage, lasting for about 600 hours and 1000 hours, respectively. Even at a higher current density of 0.5 mA cm -2 , the symmetric battery with PI@COF maintained high cycle stability for up to 1000 hours, which means that a continuous and uniform deposition behavior of ion flux has been created. These results indicate that the positive effect of PI@COF promotes the uniform transport of Li + , ultimately forming a stable interface layer and effectively reducing the interfacial resistance to Li +The resistance to transfer was significantly inhibited, and the dendrite growth during repeated electroplating and stripping processes was significantly suppressed, enhancing the stability of lithium metal batteries.
[0039] The NCM811 cathode was prepared by a slurry coating method. A slurry mixture composed of 90 wt% NCM811, 5 wt% SuperP, and 5 wt% PVDF binder in anhydrous N-methyl-2-pyrrolidone (NMP) was cast onto aluminum foil, dried at 80 °C for 1 hour, and then vacuum-dried at 120 °C overnight. The mass loading of the active material was approximately 3.0 mg cm −2 . Using the prepared cathode, solid electrolyte, and lithium metal anode, CR2032 coin cells were assembled in an argon-filled glove box. After the battery assembly was completed, charge-discharge tests were carried out to measure the capacity and Coulombic efficiency of the battery. Figure 13 Figure showing the discharge capacity of solid-state batteries with different component electrolytes at 0.2 C. From Figure 13 it can be seen that the battery with PI@COF provides a high initial discharge capacity of 180.6 mAh g -1 at 0.2 C, which is much higher than that of PI and PI@COF0.5. Figure 14 Figure showing the battery cycle stability and capacity retention data. From Figure 14 it can be seen that after 200 charge-discharge cycles of stable operation, the capacity of the battery with PI@COF remains at 156.1 mAh g -1 , showing a retention rate of 86.6% and a Coulombic efficiency of 99.0%, indicating a stable interface between the electrolyte / electrode during long cycling.
[0040] Rate capability is a key indicator for achieving higher power density. Figure 15 shows the rate capabilities of solid-state lithium metal batteries using PI, PI@COF0.5, and PI@COF electrolytes. From Figure 15 it can be seen that the current density gradually increases from 0.2 C to 0.4, 0.6, 0.8, and 1.0 C, and finally returns to 0.2 C. The discharge capacities of the battery using PI@COF are 180.2 mAh g -1 , 175.3 mAh g -1 , 161.5 mAh g -1 , 149.8 mAh g -1 , and 135.4 mAh g -1 , respectively, which are much higher than those of solid-state batteries using PI and PI@COF0.5 as solid electrolytes. This result confirms that the superionic conductivity of the PI@COF electrolyte enables solid-state lithium metal batteries to achieve high power.
[0041] In addition, it should be understood that although this specification is described according to embodiments, not every embodiment only includes an independent technical solution. This narrative way of the specification is only for clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A method for preparing a solid electrolyte for a lithium metal battery, characterized in that: The following steps are involved: Synthesis of PI: Under inert gas, 4 mmol of 2,4,6-trimethyl-1,3-phenylenediamine and 10 mL of N,N-dimethylacetamide (DMAc) were added to a three-necked flask equipped with a mechanical stirring device, and then 3.8 mmol of 4,4'-(hexafluoroisopropenyl)diphthalic anhydride (6FDA) and 0.2 mmol of 4,4'-(acetylene-1,2-diyl)diphthalic anhydride were added in sequence and mechanically stirred to generate viscous polyamic acid, and then 4.8 mL of acetic anhydride and 4 mL of pyridine were slowly added to the polyamic acid, stirred at room temperature to obtain a mixture, and the mixture was slowly poured into a methanol aqueous solution to obtain an intermediate product, the intermediate product was crushed and washed with a methanol aqueous solution, and then vacuum dried to obtain a PI polymer; Synthesis of COF: 0.15 mmol of pyromellitic acid, 0.60 mmol of benzoic acid and 0.10 mmol of 1,3,5-tris(4-aminophenyl) compound were reacted at 180-210 degrees Celsius for 5 days, the product was washed and Soxhlet extracted with tetrahydrofuran, and then vacuum dried to obtain COF; Synthesis of solid-state electrolyte: COF is immersed in 1 mol / L LiTFSI (lithium bistrifluoromethanesulfonyl imide) acetonitrile solution, washed and vacuum dried to obtain NKCOF compound, NKCOF compound, PI polymer and LiTFSI powder are dissolved in DMAc to prepare a casting solution, which is then filtered, spread and the solvent is evaporated under vacuum conditions to obtain a thin film, and finally immersed in methanol and then dried to obtain the finished product.
2. The method for preparing a solid electrolyte for a lithium metal battery according to claim 1, characterized in that: The inert gas is argon.
3. The method for preparing a solid electrolyte for a lithium metal battery according to claim 1, characterized in that: The mechanical stirring time is 48 h, and the room temperature stirring time is 24 h.
4. The method for preparing a solid electrolyte for a lithium metal battery according to claim 1 or 2, characterized in that: The volume ratio of methanol to water in the methanol aqueous solution is 1:
1.
5. The method for preparing a solid electrolyte for a lithium metal battery according to claim 1 or 3, characterized in that: The vacuum drying temperature is 80 degrees Celsius.
6. The method for preparing a solid electrolyte for a lithium metal battery according to claim 1, characterized in that: The 1,3,5-tris(4-aminophenyl) compound is one of 1,3,5-tris(4-aminophenyl)benzene, 1,3,5-tris(4-aminophenyl)oxazine and 1,3,5-tris(4-aminophenyl)amine.
7. The method for preparing a solid electrolyte for a lithium metal battery according to claim 1 or 2, characterized in that: The NKCOF compound is one of NKCOF-28, NKCOF-29 and NKCOF-30.
Citation Information
Patent Citations
Multilayer optical compensation film having reversed wavelength dispersion
CN109562593A
Full-solid-state electrolyte material, preparation method and application thereof
CN109904519A
Metal organic framework-polymer composite solid electrolyte as well as preparation method and application thereof
CN113937363A
Composite solid electrolyte, preparation method and solid lithium battery
CN114551978A
Green solid-phase synthesis method of covalent organic framework material
CN114773556A
Cited By
Functional diaphragm, preparation method thereof and lithium ion battery
CN122011477A